Pengaruh Waktu Perendaman dan Konsentrasi Giberelin (GA3) pada Pertumbuhan Benih Cemara Laut (Casuarina equisetifolia L.) - Ayuningtyas, Vici Kurnia; Tahir, Muhammad; Same, Made (Politeknik Negeri Lampung, 2017)
Gibberellin (GA3) is a natural growth hormone and synthesis used to break dormancy and accelerate germination and growth processes. The purpose of this study is to determine the effect of gibberellin concentration (GA3), soaking duration, and the interaction between gibberellin concentration (GA3) and soaking duration on the growth of australian pine tree seed. The research was conducted in State Polytechnic of Lampung from October 2015 to February 2016. This research used Factorial Randomized Block Design (RBD). The first factor is the concentration of gibberellin (GA3) namely A0 (without GA3), A1 (1000 mg.l-1 GA3), A2 (1250 mg.l-1 GA3), and A3 (1500 mg.l-1 GA3). The second factor is the soaking duration of GA3 namely B1 (soaking for 3 hours), B2 (soaking for 6 hours), and B3 (soaking for 9 hours). The result showed that GA3 at concentration 1500 mg.l-1 increased germination, the percentage of germinated seeds, hypocotyl diameter, hypocotyl length, growth homogenity, and vigor of australian pine tree seed. Soaking duration for 9 hours can increase germination, the percentage of germinated seeds, hypocotyl diameter, hypocotyl length, growth homogeneity, and australian pine tree seed vigor. The interaction between GA3 concentration at 1500 mg.l-1 and the soaking duration for 9 hours increased the germination, the percentage of germinated seeds, hypocotyl diameter, hypocotyl length, growth homogeneity, and australian pine tree seed vigor. Keywords: Casuarina equisetifolia L., gibberelin, seed vigor, soaking durationPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/649